Characterization of carotenoids in Rhodothermus marinus - Ron, Emanuel; Plaza, Merichel; Kristjansdottir, Thordis; Sardari, Roya; Bjornsdottir, Snaedis; Gudmundsson, Steinn; Hreggvidsson, Gudmundur Oli; Turner, Charlotta; van Niel, Ed; Nordberg Karlsson, Eva (MicrobiologyOpen, 2018)
Rhodothermus marinus, a marine aerobic thermophile, was first isolated from an intertidal hot spring in Iceland. In recent years, the R. marinus strain PRI 493 has been genetically modified, which opens up possibilities for targeted metabolic engineering of the species, such as of the carotenoid biosynthetic pathway. In this study, the carotenoids of the R. marinus type-strain DSM 4252T, strain DSM 4253, and strain PRI 493 were characterized. Bioreactor cultivations were used for pressurized liquid extraction and analyzed by ultra-high performance supercritical fluid chromatography with diode array and quadropole time-of-flight mass spectrometry detection (UHPSFC-DAD-QTOF/MS). Salinixanthin, a carotenoid originally found in Salinibacter ruber and previously detected in strain DSM 4253, was identified in all three R. marinus strains, both in the hydroxylated and nonhydroxylated form. Furthermore, an additional and structurally distinct carotenoid was detected in the three strains. MS/MS fragmentation implied that the mass difference between salinixanthin and the novel carotenoid structure corresponded to the absence of a 4-keto group on the ß-ionone ring. The study confirmed the lack of carotenoids for the strain SB-71 (ΔtrpBΔpurAcrtBI’::trpB) in which genes encoding two enzymes of the proposed pathway are partially deleted. Moreover, antioxidant capacity was detected in extracts of all the examined R. marinus strains and found to be 2–4 times lower for the knock-out strain SB-71. A gene cluster with 11 genes in two operons in the R. marinusDSM 4252T genome was identified and analyzed, in which several genes were matched with carotenoid biosynthetic pathway genes in other organisms.